CRIMINOLOGICAL & FORENSIC PSYCHOLOGY - Gavin, Helen, author (London : Sage, 2019)
The second edition of Criminological and Forensic Psychology is an even more theoretically rigorous, practically relevant, engaging and fun introduction to this broad and fascinating field. It covers both the conceptual basis within which psychology knowledge is applied in forensic contexts and the practical applications of psychology to the criminal civil justice systems. Case studies feature in every chapter and place students in the full context of a criminal case, showing them how psychological theories can be used to explain real-life crimes. In-depth exploration of the fascinating courtroom process including separate chapters on the Defendant's Mind and The Jury. A dedicated chapter on research methods specific to forensic psychology to help students do their research project around this topic, covering the final year and post-graduate research. A new chapter on Intimate relationship aggression: Domestic Violence and Domestic Homicide. Online resources including chapter-by-chapter multiple choice questions, additional case studies and links to further readings.